Legal Implications of Notary's Responsibility for Unlawful Acts in The Making of Authentic Deeds - Purwanti, Indah; Suwondo, Denny (Sultan Agung Notary Law Review, 2025)
Notaries as public officials are legally authorized to provide public services to the community, especially in the preparation of valid deeds that serve as flawless evidence. Article 1868 of the Civil Code stipulates that an authentic deed is a deed made in a form determined by law by or before a public official authorized for that purpose at the place where the deed was made. This thesis aims to determine the legal considerations of a Notary's unlawful acts in making authentic deeds and to determine the implications of notary liability for unlawful acts in making authentic deeds (Civil Case Study No. 259/Pdt.G/2020/PN Gin). The approach method used in this research is a normative juridical approach. The research specifications used are descriptive analysis, primary and secondary data sources, and qualitative analysis. This paper analyzes the problem with the theory of legal certainty and the theory of legal responsibility. Based on the research results in this study, the Gianyar District Court delegation Number 259/Pdt.G/2020/PN Gin emphasized that notaries as public officials have full responsibility for the accuracy of the form and content of the deeds they make. In this case, the notary was deemed negligent because he made several deeds used to legalize the "borrowed name" agreement between a foreign citizen and an Indonesian citizen, which is clearly prohibited by Article 26 paragraph (2) of the UUPA. Although the deed met the formal requirements, its substance was contrary to the law so that it was null and void and lost its authenticity. This negligence fulfills the elements of an unlawful act based on Article 1365 of the Civil Code and violates the obligations of office in Law Number 2 of 2014 concerning the Position of Notary. This decision emphasizes that notaries can be held accountable for civil, administrative, and criminal matters when the deeds they make cause losses and are contrary to the law. Therefore, notaries are obliged to uphold the principles of caution, honesty, and integrity to ensure that every deed is formally and substantially valid, so as to be able to realize legal certainty and justice for the community.